Partial femoral head replacement: a new innovative hip-preserving approach for treating osteonecrosis of the femoral head and its finite element analysis - Yang, Yanjiang; Cheng, Xiaodong; Chen, Wei; Li, Guimiao; Wang, Yuchuan; Sun, Weiyi; An, Wen; Zhang, Qi; Zhang, Yingze (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: Controversy remains regarding the optimal treatment for stage III Osteonecrosis of the femoral head (ONFH). This study presents, for the first time, the precise treatment of stage III ONFH using the "substitute the beam for a pillar" technique and performs a comparative finite element analysis with other hip-preserving procedures. Methods: A formalin-preserved femur of male cadavers was selected to obtain the CT scan data of femur. The proximal femur model was reconstructed and assembled using Mimics 20.0, Geomagic, and UG-NX 12.0 software with four different implant types: simple core decompression, fibula implantation, porous tantalum rod implantation, and partial replacement prosthesis. The finite element simulations were conducted to simulate the normal walking gait, and the stress distribution and displacement data of the femur and the implant model were obtained.The peak von Mises stress of the femoral head and proximal femur in the partial replacement of the femoral head (PRFH) group were 22.8 MPa and 37.4 MPa, respectively, which were 3.1 -38.6% and 12.8 -37.4% lower than those of the other three surgical methods.The PRFH group exhibits better mechanical performance, reducing stress and displacement in the ONFH area, thus maintaining femoral head stability. Among the four hippreserving approaches, from a biomechanical perspective, PRFH offers a new option for treating ONFH.